Effect of chemotherapy on serum nitric oxide levels in advanced stage breast cancer patients - Kadam, Charushila Y.; Abhang, Subodhini A. (International Journal of Research in Medical Sciences, 2019)
Background: The role of nitric oxide is still unclear in advanced breast cancer patients undergoing adjuvant chemotherapy. This study was undertaken to investigate the effect of chemotherapy on serum nitric oxide levels in advanced stage breast cancer patients. Methods: In this observational study, clinically and histopathologically proven sixty female patients with advanced stage breast cancer were included. According to Tumor-Node-Metastasis (TNM) classification, patients were further grouped as stage III and stage IV. Thirty healthy and age-matched female controls were selected for comparison. Blood was collected from healthy controls and from breast cancer patients after surgery prior to chemotherapy and after three weeks of administration of first adjuvant chemotherapy cycle. Serum nitric oxide levels were measured by spectrophotometric method. Results: Significantly higher concentrations of serum nitric oxide were observed in breast cancer patients before chemotherapy in stage III (p<0.0001) and stage IV (p<0.0001) of the disease as compare to concentrations in healthy controls. The serum levels of nitric oxide were significantly decreased in stage III as well as stage IV of breast cancer patients after three weeks of receiving first adjuvant chemotherapy cycle as compare to levels before chemotherapy (p<0.0001), however serum nitric oxide levels were higher in stage III (p=0.0036) and stage IV (p<0.0001) of the disease as compare to healthy controls. Conclusions: Chemotherapy drug administration causes decrease in serum nitric oxide levels in advanced stages of breast cancer patients. Monitoring serum nitric oxide levels could be used to predict patients’ response to chemotherapy treatment in breast cancer.